1995
DOI: 10.1115/1.2822615
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Hyperbolic Heat Conduction in Processed Meat

Abstract: The objective of this paper is to present experimental evidence of the wave nature of heat propagation in processed meat and to demonstrate that the hyperbolic heat conduction model is an accurate representation, on a macroscopic level, of the heat conduction process in such biological material. The value of the characteristic thermal time of a specific material, processed bologna meat, is determined experimentally. As a part of the work different thermophysical properties are also measured. The measured tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
288
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 559 publications
(304 citation statements)
references
References 11 publications
8
288
3
5
Order By: Relevance
“…Although Mitra et al [13] measured values around 16 s in processed meat, Ali & Zhang's [12] reported a smaller value. Likewise, Kaminski [7] reported a relaxation time between 20 s and 30 s for meat products and Vedavarz et al [27] found an interval between 1 s and 100 s for some biological tissues at room temperature.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Although Mitra et al [13] measured values around 16 s in processed meat, Ali & Zhang's [12] reported a smaller value. Likewise, Kaminski [7] reported a relaxation time between 20 s and 30 s for meat products and Vedavarz et al [27] found an interval between 1 s and 100 s for some biological tissues at room temperature.…”
Section: Discussionmentioning
confidence: 92%
“…However, Ali & Zhang [12] also point out that these relations are for metals and perfect structures. On the other hand, non-homogeneous materials, such as biological tissues, have very long relaxation times, and consequently would have very low heating speeds [7,13]. Unfortunately, no experimental data have been published to date on the speed of heat propagation in biological tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later on, another three new formulations of thermoelasticity based on entropy balance inequality have been proposed by Green and Naghdi [5][6][7]. Several experimental studies [8][9][10] also indicate the actual occurrence of wave type heat transport. Subsequently, several investigations [11][12][13][14][15][16] are carried out on the basis of different generalized theories of thermoelasticity.…”
Section: Introductionmentioning
confidence: 99%